1998
DOI: 10.1021/bi980711y
|View full text |Cite
|
Sign up to set email alerts
|

NMR Solution Structure of the N3‘ → P5‘ Phosphoramidate Duplex d(CGCGAATTCGCG)2 by the Iterative Relaxation Matrix Approach

Abstract: High-resolution 2D NMR spectra of the duplex CGCGAATTCGCG with deoxyribose sugars but with the normal phosphodiester linker replaced by an N3' --> P5' phosphoramidate (NP) group have been used to establish a solution structure for the duplex. Distance, angle, and base pair hydrogen-bonding constraints were used to refine the structure by use of the iterative relaxation matrix approach (IRMA). The phosphoramidate NH proton signal could be observed in DMSO at low temperature but not in H2O and D2O. For this reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
39
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…This conclusion is further supported by CD experiments on both complexes (data not shown). Only slight differences in CD spectra are observed, which likely originate from those reported in the structure of an A-type helix NP-DNA duplex (22).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This conclusion is further supported by CD experiments on both complexes (data not shown). Only slight differences in CD spectra are observed, which likely originate from those reported in the structure of an A-type helix NP-DNA duplex (22).…”
Section: Discussionmentioning
confidence: 60%
“…Synthesis of N3Ј 3 P5Ј phosphoramidate oligodeoxynucleotides (NP-DNA), which are resistant to digestion by snake venom phosphodiesterase and by nucleases in HeLa cell nuclear extract, has been described (20,21). NMR experiments showed that a NP-DNA duplex d(CGCGAATTCGCG) 2 adopts an A-type helix conformation in solution (22), suggesting that NP-DNA could be used as RNA mimetics. To ascertain this possibility, a NP-DNA version of the anti-TAR RNA hairpin aptamer was synthesized.…”
mentioning
confidence: 99%
“…P5' phosphoramidates [19] [20]. In contrast, the 3'-hydroxy-2'-deoxy nucleosides prefer C2'-endo, or S-type, conformations under similar experimental conditions.…”
mentioning
confidence: 91%
“…P5' internucleoside phosphoramidate linkages [17]. This phosphoramidate duplex adopts a RNA-like A-type double helix [17] [20]. Additionally, X-ray analysis revealed a more extensive hydration pattern of the oligonucleotide phosphoramidate sugar-phosphate backbone compared to that for the phosphodiester counterpart.…”
mentioning
confidence: 99%
See 1 more Smart Citation